2016
DOI: 10.1080/00140139.2015.1122234
|View full text |Cite
|
Sign up to set email alerts
|

The stress and workload of virtual reality training: the effects of presence, immersion and flow

Abstract: The present investigation evaluated the effects of virtual reality (VR) training on the performance, perceived workload and stress response to a live training exercise in a sample of Soldiers. We also examined the relationship between the perceptions of that same VR as measured by engagement, immersion, presence, flow, perceived utility and ease of use with the performance, workload and stress reported on the live training task. To a degree, these latter relationships were moderated by task performance, as mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 19 publications
4
29
0
1
Order By: Relevance
“…Then, they had to put three sugar cubes in a cup with sugar tongs, put the tongs back on a towel and fold it, cut a sheet of paper, and finally move a tray to the other end of the table. VR pre-training is important to limit mental load effects and stress that can result from an initial VR experience (Lackey, Salcedo, Szalma, & Hancock, 2016). As it was assumed that most of the participants were novices in VR, this scenario was performed twice.…”
Section: Pre-training Sessionmentioning
confidence: 99%
“…Then, they had to put three sugar cubes in a cup with sugar tongs, put the tongs back on a towel and fold it, cut a sheet of paper, and finally move a tray to the other end of the table. VR pre-training is important to limit mental load effects and stress that can result from an initial VR experience (Lackey, Salcedo, Szalma, & Hancock, 2016). As it was assumed that most of the participants were novices in VR, this scenario was performed twice.…”
Section: Pre-training Sessionmentioning
confidence: 99%
“…The NASA Task Load Index (TLX) is a method to let a user estimate the experienced workload when operating an interactive system (Hart and Staveland 1988;Hart 2006), and has been applied for VR and input technology scenarios in different contexts before (Lackey et al 2016;Bachmann et al 2018). The TLX investigates six factors, namely physical demand, mental demand, temporal demand, effort, frustration, and the user's perceived own performance.…”
Section: Nasa Task Load Index (Tlx)mentioning
confidence: 99%
“…Presence was included in the simulation-specific workload measure, as presence or immersion is thought to be important for motivation and engagement with VR simulation training (Stanney et al 2003). It has been suggested that presence in VR may reduce cognitive load, as less attentional effort has to be expended to consciously focus on the task (Wickens 1992), and Lackey et al (2016) found that immersion correlated with additional mental demands. Alternatively, Rose et al (2000) have suggested that VR might impose additional load when the user has to cope with mismatches of visual feedback and vestibular and proprioceptive feedback.…”
Section: Discussionmentioning
confidence: 99%